A novel "lateral approach short axis in-plane" technique vs. conventional "short-axis out-of-plane approach" for ultrasound-guided internal jugular vein access: a prospective randomized non-inferiority trial - Kalina, Michal; Vargová, Patricia; Bubeníková, Adéla; Škulec, Roman; Černý, Vladimír; Astapenko, David (The ultrasound journal, 2025)
BACKGROUND: The cannulation of the internal jugular vein (IJV) is a frequent procedure in critically ill patients. According to the guidelines, real-time ultrasound navigation is recommended. Traditional techniques pose several disadvantages, such as suboptimal needle visualization. Therefore, this non-inferiority trial aimed to describe the novel approach and compare the novel lateral in-plane short-axis approach for IJV access with the conventional short-axis out-of-plane approach. OBJECTIVES: The primary objective of the trial was to prove that the first attempt success rate in the novel technique is non-inferior to the conventional technique. The secondary objectives were to demonstrate that the complication rate and the functional duration of the catheter in the novel technique are not inferior to those in the conventional technique. METHODS: Patients eligible for IJV cannulation were randomly assigned to either the novel technique (Group A) or the conventional one (Group B). The procedure duration, success rate and the number of attempts required were documented. The functionality of the catheter and complications were monitored from insertion until the catheter removal. Standard descriptive statistical methods were employed for the analysis. RESULTS: A total of 200 subjects were equally divided between Group A and Group B. For the primary outcome, there was no significant difference in first attempt success rate (Group A: 79, Group B: 77, p = 0.434). Secondary outcomes, including complications and catheter functional time, did not differ significantly between the groups. However, the novel technique demonstrated a significantly faster procedure time (Group A: 315 s, Group B: 330 s, p = 0.016). Notably, the novel approach was linked with significantly larger IJV diameter measured during the procedure (Group A: 18.2 mm, Group B: 12.1 mm, p < 0.001). CONCLUSION: The novel lateral in-plane short-axis approach for IJV cannulation is a non-inferior alternative with a lower incidence of posterior vessel wall puncture compared to the conventional approach.
Keywords: Point of care ultrasound; Centrally inserted venous catheter; Jugular vein; Ultrasound; Cannulation